ANALISIS KINERJA TENAGA MEDIS PUSKESMAS KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Mitriadi Saputra; Tuti Khairani Harahap (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Performance Medical is to provide nursing services to individuals, families, groups or communities according diagnose problems that occur from a problem that is both simple to complex.Kampar District Government strongly supports the health program. In this study discusses the performance of medical personnel in the northern Kampar district health centers. Still the complaints of patients with medical personnel were slow, doctors were minimal, doctors often do not exist in the clinic during working hours make less than the maximum performance of medical personnel. The problem in this research is how the performance of medical personnel northern Kampar district health centers, the factors that hinder the performance of medical personnel northern Kampar district health centers. For the purpose of this study to determine and analyze the performance of medical personnel in Kampar District Health Clinics North, to identify and analyze the factors that hinder the performance of medical personnel in Kampar District Health Clinics North.This study uses the theory of Anwar Prabu Mangkunegara to know how the quality, quantity, duties and responsibilities of the performance of medical personnel in the northern Kampar district health centers. Type of this research is qualitative descriptive method which uses a sampling technique with snowball sampling. Informants in this study is the northern Kampar district health clinic, medical personnel and the public or patients.Performance of medical personnel in health centers North Kampar not maximum , based on the results of interviews that researchers do to patients , residents , and family parties . Based on the indicators put forward by Anwar King Mangkunegara in the category of quality and quality of North Kampar district health centers are still not yet been reached . While the category of responsibility and execution of tasks northern Kampar district health center has been reached . Then the overall performance of the medical tenga North Kampar district health centers is not maximized because there are still shortcomings and does not run pursuant to the Standard Operational Procedures ( SOP ) has been determined.Keywords: Performance, Medical Personnel